Stratigraphy, palynology, and conchostracans of a Lower Cretaceous sequence at the Cañadón Calcáreo locality, Extra-Andean central Patagonia: age and palaeoenvironmental significance - Volkheimer, Wolfang (2008)
The first palynologic record in a Lower Cretaceous sequence at the Cañadón Calcáreo locality of Extra-Andean central Patagonia is presented. It contributes a more precise chronology and palaeoenvironmental characterization of the sequence. The conchostracan faunal records support the palynologic results. Sedimentary environments are studied in relation to a tectogenetic development model. Detailed measurement of stratigraphic/sedimentologic sections in the field was complemented by sampling for palynology, conchostracans and sedimentary facies/microfacies analysis. The depositional environment is lacustrine/palustrine in the lower part, grading to fluvial. The middle and upper sections of the unit are fluvial and characterized by prevailing sandstones, conglomerates and tuffs. Dominant genera of the palynoflora are Classopollis and Callialasporites, with an incipient presence of Cyclusphaera. The prevalence of the thermophilous genus Classopollis indicates warm climatic conditions, and the high frequency and diversity of trilete spores, corresponding to a hygrophile vegetation of ferns and bryophytes, indicates locally humid conditions. The fauna of conchostracans identified is composed of species of the genera Nemestheria (Zhestheria), Pseudestherites, Euestheria?, and probably Congestheriella. A Valanginian age is inferred for the middle part of the sequence.